Bitter Taste Receptors for Asthma Therapeutics - Nayak, Ajay P.; Shah, Sushrut D.; Michael, James V.; Deshpande, Deepak A. (Frontiers in Physiology, 2019)
Clinical management of asthma and chronic obstructive pulmonary disease (COPD) has primarily relied on the use of beta 2 adrenergic receptor agonists (bronchodilators) and corticosteroids, and more recently, monoclonal antibody therapies (biologics) targeting specific cytokines and their functions. Although these approaches provide relief from exacerbations, questions remain on their long-term efficacy and safety. Furthermore, current therapeutics do not address progressive airway remodeling (AR), a key pathological feature of severe obstructive lung disease. Strikingly, agonists of the bitter taste receptors (TAS2Rs) deliver robust bronchodilation, curtail allergen-induced inflammatory responses in the airways and regulate airway smooth muscle (ASM) cell proliferation and mitigating features of AR in vitro and in animal models. The scope of this review is to provide a comprehensive and systematic insight into our current understanding of TAS2Rs with an emphasis on the molecular events that ensue TAS2R activation in distinct airway cell types and expand on the pleiotropic effects of TAS2R targeting in mitigating various pathological features of obstructive lung diseases. Finally, we will discuss specific opportunities that could help the development of selective agonists for specific TAS2R subtypes in the treatment of asthma.